Faktor-Faktor yang Mempengaruhi Tingkat Kepuasan Pelanggan dan Loyalitas Pelanggan Terhadap Layanan Transportasi Online di Kota Batam - Adhitomo Wirawan; Putri Saraswati Naufalita Ryanto; Mia Syafrina; Fuad Arif Rahman; Alrido Martha Devano; Fitriana Aidnilla Sinambela (Politeknik Negeri Batam, 2023)
By evaluating and identifying variables from the variables evaluated, this research investigates the complexity of factors that affect users of online transportation services' satisfaction and loyalty. A questionnaire was selected as the data gathering strategy and tool for the quantitative investigation. PLS-SEM, or partial least squares structural equation modeling, was used to analyze the given data. The findings demonstrate that two factors—perceived app benefits and perceived service quality—can be significantly used to predict consumer loyalty and happiness while utilizing online transportation services, particularly Go-ride and Grab bike services. Customer happiness is unaffected significantly by the perceived sales promotion component, but customer loyalty is significantly impacted. Meanwhile, the effect of customer satisfaction on customer loyalty has a positive but insignificant effect.